Transformation of Pro-Leu-Gly-NH(2) Peptidomimetic Positive Allosteric Modulators of the Dopamine D(2) Receptor into Negative Modulators - Bhagwanth, Swapna (American Chemical Society, 2012)
[Image: see text] The synthesis of dimethyl derivatives of 5.6.5 spiro bicyclic lactam Pro-Leu-Gly-NH(2) peptidomimetics was carried out to test the hypothesis that by placing methyl groups on the β-methylene carbon of the thiazolidine ring steric bulk would be introduced into the topological space that the β-methylene carbon is believed to occupy in the negative allosteric modulators of the dopamine D(2) receptor. With such a modification, a positive allosteric modulator would be converted into a negative allosteric modulator. This hypothesis was shown to be correct as 3a and 4a where found to be negative allosteric modulators, whereas their unmethylated derivatives were positive allosteric modulators of the dopamine D(2) receptor.